Electropolymerization and characterization of Poly(3,4-ethylenedioxythiophene, polyaniline, polypyrrole and thier copolymers - Kulandaivalu, Shalini (2015)
In recent years, conducting polymers have served as a core material for many new applications such as sensors, solar cells and electrochromic display devices. Among the methods to prepare conducting polymers (CPs), electrochemical method is the simplest and most cost effective. In this thesis, electropolymerization and characterization of three different CPs namely poly(3,4-ethylenedioxythiophene) (PEDOT), polyaniline (PANI) and polypyrrole (PPy) and its copolymer, PEDOT/PANI and PEDOT/PPy were studied. The effect of applied potentials, Ep (1.0 V to 2.0 V vs. Ag/AgCl) and monomer concentrations (1 mM, 5 mM and 10 mM) on prepared polymers films were investigated. The electrochemical polymerization of EDOT, ANI and Py were performed potentiostatically at different Ep for 5 minutes in aqueous solution in the presence of lithium perchlorate (LiClO4) as supporting electrolyte. A new approach was used to perform the electrochemical copolymerization process of EDOT with ANI and EDOT with Py. The copolymer film was prepared at the potential obtained from the intercept points in the forward scan of cyclic voltammetry of the both corresponding monomers. A series of copolymer films were also electropolymerized at different EDOT/ANI and EDOT/Py concentration ratios at different Ep in aqueous solution containing LiClO4. The FTIR and Raman spectra confirmed the formation of homopolymers and copolymers. While, the morphology studies showed different structures of homopolymer and copolymers were obtained at different concentrations and Ep. The electrochemical properties of the resultant polymer films were further analyzed using cyclic voltammetry (CV) and electrical impedance spectroscopy (EIS). High specific capacitance and low charge transfer resistances, Rct were obtained for films with globular structures. The impedance studies of these films show lower Rct at Ep of 2.0 V. Electrochemical studies for copolymers revealed that specific capacitance and Rct values are significantly affected after the incorporation of ANI (or Py) into EDOT. Few equivalent circuit models were used to fit the impedance spectra of homopolymers and copolymer where the spectra were fitted well. The morphologies and electrochemical properties of the homopolymers and copolymer are significantly influence by monomer concentration and Ep. Based on the work reported in this thesis, the comparative studies of FTIR and Raman spectroscopy, scanning electron microscopy (SEM), CV and EIS for PEDOT, PANI and PPy films illustrate that the films shows adherent and homogenous morphologies as well good electrochemical properties at 1.0 V and 10 mM conditions.